A SYNTACTICAL ANALYSIS OF SONG LYRICS “SAY YOU LOVE ME” BY JESSIE WARE - Syuriadi, Roesitha D M; Englishtina, Inti (Universitas 17 Agustus 1945 Semarang, 2023)
This study is a linguistic analysis that discusses sentence patterns of syntactical fields of song lyrics “Say You Love Me” by Jessie Ware that uses trees diagram. Jessie Ware is an English singer, songwriter, and podcaster. The theories are used to find sentence patterns refer to transformational generative grammar (TGG) theory by Noam Chomsky, the theory of phrase structure from Goodman, and the tree diagram theory by Bornstein. The research method used is the descriptive qualitative method. The data source of this study is Jessie Ware’s song and to collect the data, the writer chooses “Say You Love Me” The result shows that there are 6 syntactical structures that are dominant in 18 lines, and there are 4 syntactical structures composed of different pattern constructions found in 5 lines in Jessie Ware’s song lyrics “Say You Love Me”. Data as follows. There are 6 categories of dominant syntactical structures which used in the three songs of Jessie Ware’s song lyrics namely (1) S ⇨ NP + VP in 5 lines, (2) S ⇨ VP + NP in 4 lines, (3) S ⇨ Conj + NP +VP in 4 lines, (4) S ⇨ Conj +VP + NP in 2 lines, (5) S ⇨ S + Conj + S in 2 lines, and (6) S ⇨ VP + Conj + NP in 1 line. There are 5 other syntactical structure categories also founded in these songs, namely (7) S ⇨ Conj +Adj P + VP in 1 line, (8) S ⇨ Conj + adj P + NP + VP in 1 line, (9) S ⇨ Adj P + NP + PP in 1 line, (10) S ⇨ Adv P + VP + NP in 2 lines. Also, the writer identified the following syntactical structure as having the highest frequency in Jessie Ware's song lyrics “Say You Love Me” from the result above (1) S ⇨ NP + VP in 5 lines, (2) S ⇨ VP + NP in 4 lines. (3) S ⇨ Conj + NP +VP in 4 lines. On the other hand, the less common syntactical structures are (4) S ⇨ Conj +VP + NP in 2 lines, (5) S ⇨ S + Conj + S in 2 lines, and (6) S ⇨ VP + Conj + NP in 1 line. (7) S ⇨ Conj +Adj P +VP in 1 line, (8) S ⇨ Conj + Adj P + NP +VP in 1 lne, (9) S ⇨ Adj P + NP +PP in 1 line, (10) S ⇨ Adv P + VP +NP in 2 lines. From the result above, the writer suggests that this research could be continued by future writer or researcher and that it might be utilized as a resource for learning about syntax in the hopes that it will be interested to the reader.Keywords: Jessie Ware’s song lyrics, syntactical analysis